Comparing the impact of social support on the life satisfaction of widowed and non-widowed elders - Tian, Hua; Chen, Jie (Frontiers in Psychology, 2022)
Aim To compare differences in life satisfaction between widowed and non-widowed elders based on social support. Methods A total of 4,560 widowed and 3,655 non-widowed elders were selected from the Chinese Longitudinal Healthy Longevity Survey (CLHLS-2018). Ordinal logistic regression models and t-tests were performed using SPSS v20. Results Both widowed and non-widowed elders had high levels of life satisfaction. Personal characteristics had a significant impact on the life satisfaction of both widowed and non-widowed elders. Endowment insurance, social trust, residence, self-rated health, and living with family had a significant impact on the life satisfaction of widowed elders (p < 0.001), while endowment insurance, government subsidy, and self-rated health significantly impacted non-widowed elders (p < 0.001). Self-rated health had the greatest impact on the life satisfaction of widowed and non-widowed elders (OR = 4.62/4.45), followed by endowment insurance (OR = 1.24/1.32). Conclusion Social support can significantly improve life satisfaction, but its impact is heterogeneous. Informal social support plays a greater role in improving the life satisfaction of widowed elders, but formal social support plays a greater role in the life satisfaction of non-widowed elders.